TRANSNATIONAL CRIME ILEGAL IMPORTING DAGING DI PERBATASAN WILAYAH BENGKALIS-MALAYSIA : STUDI KASUS PADA BEACUKAI BENGKALIS - Nirwana, Nadia Putri; Rinaldi, Kasmanto (Gapenas Publisher, 2024)
Indonesia is a maritime country with vast sea territory, which has led to the phenomenon of illegal imports in several areas, including Bengkalis. This study aims to examine the factors causing meat smuggling in Bengkalis and the preventive efforts made by the Bengkalis Customs. Using a descriptive qualitative approach, the research found that Bengkalis' geographical location, high import duty rates, and domestic demand prices trigger smuggling. Preventive efforts by Customs and Police include: a) sea and coastal patrols; b) food availability surveys with Disperindag; c) socialisation to the community to secure the area